ANALYSIS OF TEACHER'S DIFFICULTY IN APPLYING LEARNING WITH THESAINTIFIC APPROACH - Lisa Rahmayanti; Zariul Antosa; M.Jaya Adiputra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The scientific approach is one of the learning methods that must be implemented in the 2013 curriculum. However, in practice, not all teachers are able to apply the scientific approach in every learning process. This occurs because some teachers still experience difficulties in its application, and others do not fully understand the conceptual meaning of each step within the scientific approach. This descriptive qualitative study aims to identify and collect the factors contributing to teachers’ difficulties in using learning activities based on the scientific approach at SD Negeri 30 Pekanbaru. Data were collected through observation, interviews, and documentation, and analyzed using data reduction techniques. The results show that teachers at SD Negeri 30 Pekanbaru still face obstacles in implementing various activities required in the scientific approach. This is evident from several stages that were not carried out, such as the observing stage in Grades I, II, III, and IV during the first and third observations, and in Grade V during the first observation. Experimental activities were also not implemented in Grades II and III during the first and third observations. Furthermore, communication activities were not conducted in Grade I, in all observations in Grade II, and in Grades III during the first and second observations.